FAMILY-RELATED DETERMINANTS SHAPING EMOTIONAL BEHAVIOR IN CHILDREN - Fitriari, Tutfah Razzak; Irwanto (UNIVERSITAS AIRLANGGA, 2025)
Background: Emotional behavior in children is rarely addressed through early screening, despite its importance in child development. The family plays a central role; however, prior studies vary in the family aspects they examine, with some factors receiving more attention than others. This review aims to synthesize which family-related determinants are most frequently studied about children’s emotional behavior. Method: A literature search was conducted using the keywords “family” AND “child*” AND “emotional OR behavior” AND “internalizing OR externalizing,” limited to English-language, full-text, open-access articles published between 2020 and 2025. Databases included ScienceDirect, PubMed, and Google Scholar. The PICO framework guided the research question. A total of 1,449 articles were initially identified. Elicit (elicit.com) was used to assist the screening and selection process. After applying inclusion and exclusion criteria, seven articles were eligible for review. Result: The seven studies examined various family-related factors influencing children’s emotional and behavioral outcomes. Recurring themes included parenting style, family conflict, parenting stress, parental mental health, and family structure. Supportive parenting, consistent routines, and a positive emotional climate were associated with better emotional regulation, while harsh discipline, conflict, and poor parental mental health were linked to greater emotional and behavioral problems. Some studies identified mediating or moderating factors such as resilience, sleep quality, and neural responses, reflecting the complex interplay between family environments and child development. Conclusion: Children’s emotional and behavioral development is shaped by multiple interrelated family factors. Interventions should be multidimensional, addressing parenting practices, caregiver mental health, and household stability to support child well-being.